Atomic structures of anthrax toxin protective antigen channels bound to partially unfolded lethal and edema factors - Nathan J. Hardenbrook (Nature Portfolio, 2020)
The bacterial translocase channel anthrax toxin is composed of the protective antigen (PA) that forms a translocase channel and two cytotoxic enzymes: lethal factor (LF) and edema factor (EF), which go through the PA channel to enter host cells. Here the authors provide mechanistic insights into LF and EF translocation by determining the cryo-EM structures of the anthrax toxin transmembrane channel protein in complex with LF and EF.